2011
DOI: 10.1292/jvms.10-0163
|View full text |Cite
|
Sign up to set email alerts
|

Starfish, Asterias amurensis and Asterina pectinifera, as Potential Sources of Th1 Immunity-Stimulating Adjuvants

Abstract: ABSTRACT. Saponin is the generic name of steroid or triterpene glycosides, and the capacities of some saponins to stimulate both Th1 immune response and production of cytotoxic T cells are useful as vaccine components against intracellular pathogens. Because saponins have been found commonly in starfish, we assessed the potential of starfish, Asterias amurensis and Asterina pectinifera, as adjuvant sources. Crude starfish saponins had hemolytic activities (EC 50 =10 to 100 μg/ml) and thin layer chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Among the serum antibody IgG subtypes, the IgG1 is a marker dominated by Th2-type immune responses, whereas IgG2b is associated with Th1-type immunity ( 22 , 23 ). To analyze which T cell response is preferentially boosted by ABP-AW1, the serum levels of OVA-specific IgG1 and IgG2b were measured using an ELISA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the serum antibody IgG subtypes, the IgG1 is a marker dominated by Th2-type immune responses, whereas IgG2b is associated with Th1-type immunity ( 22 , 23 ). To analyze which T cell response is preferentially boosted by ABP-AW1, the serum levels of OVA-specific IgG1 and IgG2b were measured using an ELISA ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2) were elevated significantly in the OVA/alum and OVA/ABP-AW1 groups compared with the OVA alone group. The IgG1 subtype is reported to be associated with Th2-dominated immune responses, whereas IgG2b is considered to be a mediator of Th1-type immunity (33). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among the T lymphocytes, T cell responses have been divided in two subclasses, Th1 and Th2. Th1 and Th2 immune response profiles correspond to the activation of two distinct major subsets of T cells characterized by their pattern of cytokine production (29,33), i.e. IL-2, TNF-β and IFN-γ vs. IL-4, IL-5 and IL-10, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plants have been the main sources of bioactive saponins, starfish are also a desirable source, because about 400 structurally different saponins have been purified from starfish and their diverse bioactivities such as cytotoxic, hemolytic, ichthyotoxic, antifungal, antiviral and anti-inflammatory activities have been reported [4]. Recently, we have investigated the potential of starfish saponins as immunological adjuvants and found that the crude extract from two common littoral species, Asterias amurensis and Patiria (or Asterina) pectinifera, promoted antibody production when they were subcutaneously injected into mice together with the antigen, ovalbumin (OVA) [5]. Accordingly, in this research, we purified the saponin from P. pectinifera and evaluated its adjuvant activity.…”
mentioning
confidence: 99%